A materialidade da Educação do Campo e sua incidência nos processos formativos que a sustentam: uma análise acerca do curso de Pedagogia da Terra na UNIOESTE - Verdério, Alex (2011)
This dissertation is about the formation of land educators in graduation courses, to do so, it takes as study object the Pedagogy of the Land Course at State University of the West of Paraná UNIOESTE, Antonio Gramsci Group. It has as reference the materiality of the Land Education - LE, in the perspective to analyze the formative process, outlined on the tension exercised on bourgeois state, so that it ensures the universality of the rights to education also for the people from the land. The present research considered the proposition, the creation and the configuration of the graduation course of Pedagogy for Educators of the Land, Class I, from UNIOESTE and this analyzes perspective allowed the comprehension of the trajectory of the LE, considering its history, its theoretical bases and its practices on the formation of the land educators, whose process was developed in this graduation course, organized from the regime of the interchange that consist in time/space course-school and time/space community-school of the land. The study object was getting enlarged in the dimension that was being indentified with the class struggle. In this way, the trajectory of the present research permitted understand the fight for an LE, as a propose that is being materialized through the collective struggle and the education practice of the people from the field, through Popular Social Movements from the Land - PSML, in the perspective to ensure rights. This panorama make us reflect about the process that population from the land have been effected as protagonists, process that, from the collective experience in the context of classes struggles, explicit their formative character. This dissertation is organized in three chapters. In the first one, the elaboration followed the characterization of the movement of the reality that generated the struggle for an LE, achievement that permitted the formulation of some goals that were denominated as boundaries of LE, that later, produced a necessary contour to comprehend the trajectory and the actuality of a struggle for an LE in Brazil. In the second chapter, the way of elaboration passed to identify the conception of formation that orients the LE underneath the point of view of PSML, that gets fundamentally firmed in the conception of Popular Education and the Pedagogy Soviet Socialist. In the third chapter, based on the experience of the referent group, it was researched the process of proposition, creation and configuration of the course, elements that set the formative process. Under these considerations were retaken the trajectory of land educators formation from Paraná State and, the main elements about the formative process, unleashing for the formation of Antonio Gramsci Group, the point that permitted the positioning in defense and in struggle for consolidation of a formation propose of land educators in graduations courses.